E-Voting application development based on android: A case study election chairman of HIMANIFO Universitas Muhammadiyah Magelang - Siti Maesyaroh; Agus Setiawan; Sunarni Sunarni (Borobudur Informatics Review, 2021)
Election Chairman of HIMANIFO has obstacles namely the lack of students participation in the voting because they can not attend in the election, while the voting is done using paper media. Due the problems the author proposes to design and build a system of Android-based E-Voting for the election of Chairman and Deputy Chairman of HIMANIFO. The application is built using the Unified Approach development method. Applications that produced a website and Android, the web will help administrators to manage students and chairman candidate data, and receive incoming voice. Android app helps students to conduct voting. The purpose of this system is to make it easier for students to carry out the voting process and for students to participate in voting. The results of this study provide convenience in the election of students. Sudents can vote anywhere and can save paper.